Communicative of language - Rahmat Allah, Abdul Khaliq Fadl (Arab Journal for Sciences and Research Publishing, 2016)
This study defines language both for the ancient and the modern, and it cryptically clarified the importance of language which distinguishes humans from animal, which makes him a great think who is able to administer life activities, organizing it, developing it, resembling it to organize living beings, because it (language) grows, evolves, getting old, and dies if the right conditions of it is continuity and the characteristics of the always are not found for it. The study indicates to the well a sorted function which the language serves in all aspects of life like intellectuals, social, cultural, educational, psychological, communicative functions, and others. The importance of the study springs from its concerns with the language itself, and its functions towards the society particularly its communicative function. This study basically aims at portraying to the role of communicative function of language in the community. It used to be simple when man is created and it evolved by the time, and it is importance is increased after when printing is discovered in the middle of the fifteenth century AD. The communicative function of language is considered one of the most important that connects individual and the group, and together with other groups. The study follows the descriptive approach, and it comes to a member of findings, some of which: usage strengths and conditions the language communicative language strengthen and consolidate the factors. The study recommends, that there is a relation between the communicative function of the language and the consolidation of the national unity.
Keywords: communicative; language; job